TAX AVOIDANCE DAN KARAKTERISTIK OPERASIONAL PERUSAHAAN TERHADAP BIAYA HUTANG - Wiwi Idawati; Fandi Wisudarwanto (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract ˗ The purpose of this research is to obtain empirical evidence of the effect of Tax Avoidance, Institutional Ownership, Operating Cash Flow and Leverage on the Cost of Debt. This study uses a causal-comparative research method with secondary data obtained from the financial statements of property companies. The population in this study were 49 property companies listed on the Indonesia Stock Exchange. The sampling technique was purposive sampling in order to obtain a representative sample of 17 property companies. This study uses multiple regression analysis to test the hypothesis. Based on the research results indicate that Tax Avoidance and Operating Cash Flow do not have a significant effect on the cost of debt and collectively tax avoidance, institutional ownership, operating cash flow, leverage simultaneously affect the cost of debt. Keywords: Tax Avoidance; Institutional Ownership; Operating Cash Flow; Leverage; Cost of Debt